Adenoma Detection in Excellent Versus Good Bowel Preparation for Colonoscopy. Issue 4 (April 2015) - Tholey, Danielle M.; Shelton, Corbett E.; Francis, Gloria; Anantharaman, Archana; Frankel, Robert A.; Shah, Paurush; Coan, Amy; Hegarty, Sarah E.; Leiby, Benjamin E.; Kastenberg, David M.
Abstract : Goal: To determine whether Excellent bowel cleansing is superior to Good for the detection of adenomas. Background: High quality colonoscopy requires Adequate bowel preparation. However, it is unknown whether adenoma detection differs between subcategories of Adequate cleansing. Study: We utilized a retrospective, cross-sectional study design to obtain data about patients undergoing colonoscopy at a single university center between August 31, 2011 and September 1, 2012. Primary outcome was adenoma detection rate (ADR), the percentage of patients with ≥1 adenoma. Secondary outcomes included adenomas per colonoscopy, adenoma distribution (proximal vs. distal), and detection of advanced adenomas, sessile serrated polyps (SSP), and cancer. Results: The electronic medical record of 5113 consecutive colonoscopies with Good or Excellent preparation was queried for preparation quality, colonoscopy indication, demographics, medical history, and history of adenoma and colon cancer. Exclusion criteria were age below 18 years, inflammatory bowel disease, or familial polyposis. Adenoma detection was not superior with Excellent cleansing as compared with Good for ADR [respectively, 26% vs. 29%, odds ratio 0.97 (0.85, 1.11), P =0.618] or adenomas per colonoscopy [respectively, 0.437 vs. 0.499, incidence rate ratio (IRR) 0.98 (0.90, 1.07), P =0.705]. Excellent cleansing demonstrated superior detection of SSPs [IRR 1.66 (1.14, 2.40), P =0.008] and advanced adenomas [IRR 1.37 (1.09, 1.72), P =0.007] but not colon cancer [odds ratio 0.286 (0.083, 0.985), P =0.0474]. Conclusions: ADR is not significantly different between the Adequate subcategories of Excellent and Good. However, Excellent cleansing is associated with superior detection of advanced adenomas and SSPs. If confirmed, achieving an Excellent preparation may improve colonoscopy performance in the proximal colon where SSPs primarily occur.